The Political Philosophy of Rousseau - Masters, Roger D. (Book collections on Project MUSE., 1968)
This book is intended as an equivalent to or substitute for that ""more reflective reading"" which Rousseau considered essential to an understanding of his ideas. It is designed to complement perusal of the texts themselves, and the arrangement is such that chapters on each of Rousseau's major writings can be consulted separately or the commentary may be read through in sequence. The author's purpose is not to present a ""key"" to Rousseau's political philosophy, but rather to explore the works themselves in an effort to reveal Rousseau's ""system, "" from which the reader may then draw his ow.